Effects of multiannual, seasonal unconditional cash transfers on food security and dietary diversity in rural Burkina Faso: The Moderate Acute Malnutrition Out (MAM’Out) cluster-randomized controlled trial - Houngbe, Freddy; Tonguet-Papucci, Audrey; Nago, Eunice; Gauny, Josselin; Ait-Aïssa, Myriam; Huneau, Jean-François; Kolsteren, Patrick; Huybregts, Lieven (Cambridge University Press, 2019)
To evaluate the impact of multiannual, seasonal unconditional cash transfers (UCT) provided within the Moderate Acute Malnutrition Out (MAM’Out) research project on households’ food security and children’s and caregivers’ dietary diversity.A two-arm cluster-randomized controlled trial with sixteen villages in the intervention group and sixteen others in the control group. A monthly allowance of 10 000 XOF was transferred to caregivers of eligible children via a personal mobile phone account from July to November 2013 and 2014.Tapoa province in the eastern region of Burkina Faso.Data on household food access (monthly adequate household food provisioning (MAHFP); household food insecurity access scale (HFIAS)) and maternal and child dietary diversity were analysed for 1143 households, 1219 caregivers of reproductive age (15–49 years) and 1247 under-5 children from both intervention and control groups.The mean women dietary diversity score in intervention caregivers and the mean dietary diversity score (DDS) in intervention children with inadequate minimum DDS at baseline were respectively 7 % (95 % CI 2, 11 %;P= 0·002) and 17 % (95 % CI 11, 23 %;P<0·001) higher compared with the control group. However, no difference was found in the intervention effect on household food security measured with HFIAS (relative risk = 1·03; 95 % CI 0·92, 1·15;P= 0·565) and MAHFP (relative risk = 0·98; 95 % CI 0·96, 1·01;P= 0·426).Multiannual, seasonalUCT increased dietary diversity in children and their caregivers. They can be recommended in actions aiming to improve maternal and child diet diversity.